Non-coding RNA regulation of Magang geese skeletal muscle maturation via the MAPK signaling pathway - Hong, Longsheng; Xu, Danning; Li, Wanyan; Wang, Yifeng; Cao, Nan; Fu, Xinliang; Tian, Yunbo; Li, Yugu; Li, Bingxin (Frontiers in Physiology, 2024)
Skeletal muscle is a critical component of goose meat and a significant economic trait of geese. The regulatory roles of miRNAs and lncRNAs in the maturation stage of goose skeletal muscle are still unclear. Therefore, this study conducted experiments on the leg muscles of Magang geese at two stages: 3-day post-hatch (P3) and 3 months (M3). Morphological observations revealed that from P3 to M3, muscle fibers mainly underwent hypertrophy and maturation. The muscle fibers became thicker, nuclear density decreased, and nuclei moved towards the fiber edges. Additionally, this study analyzed the expression profiles of lncRNAs, miRNAs, and mRNAs during the skeletal muscle fiber maturation stage, identifying 1,949 differentially expressed mRNAs (DEMs), 21 differentially expressed miRNAs (DEMIs), and 172 differentially expressed lncRNAs (DELs). Furthermore, we performed enrichment analyses on DEMs, cis-regulatory genes of DELs, and target DEMs of DEMIs, revealing significant enrichment of signaling pathways including MAPK, PPAR, and mTOR signaling pathways. Among these, the MAPK signaling pathway was the only pathway enriched across all three types of differentially expressed RNAs, indicating its potentially more significant role in skeletal muscle maturation. Finally, this study integrated the targeting relationships between DELs, DEMs , and DEMIs from these two stages to construct a ceRNA regulatory network. These findings unveil the potential functions and mechanisms of lncRNAs and miRNAs in the growth and development of goose skeletal muscle and provide valuable references for further exploration of the mechanism underlying the maturation of Magang geese leg muscle.